Factors Associated with Histopathological Examination Findings among HPV DNA Positive Women Attending at a Tertiary Cancer Hospital of Nepal - Subedi, Hemnath; Acharya, Bijaya Chandra; Gurung, Sarita Rana; Upadhyay, Hari Prasad (Journal of Bharatpur Hospital, 2025)
Background Cervical cancer remains a major public health concern in Nepal, particularly among women infected with high-risk human papillomavirus (HPV). Histopathological examination plays a critical role in diagnosing precancerous and cancerous cervical lesions. This study aimed to assess the histopathological findings and their associated factors among HPV DNA-positive women attending a tertiary cancer hospital in Nepal. Methods A hospital-based cross-sectional study was conducted among 78 HPV DNA-positive women aged 30–60 years who visited B.P. Koirala Memorial Cancer Hospital from July 2021 to June 2022. Data were collected using a structured questionnaire, medical records, and laboratory reports. Histopathological findings were categorized into normal, cervicitis, and cervical intraepithelial neoplasia (CIN I, II, III). Descriptive statistics, chi-square tests, and binary logistic regression were used for data analysis in SPSS version 16. Results Among the 39 HPV-positive women, (61.5%) had abnormal histopathological findings, with CIN III (18%) being the most common lesion, followed by CIN I (15.4%) and cervicitis (14.1%). HPV-16 and HPV-18 were the most frequently detected genotypes. Most sociodemographic and reproductive variables were not significantly associated with histopathological outcomes. However, Liquid-Based Cytology (LBC) results showed a significant association (p < 0.001) with histopathological findings. Conclusions A high proportion of HPV-positive women had precancerous cervical lesions, especially those infected with HPV-16 and HPV-18. The study underscores the importance of integrating HPV DNA testing with cytology and histopathological evaluation for early detection and management of cervical lesions in Nepal.